Porosity of the fine fractions of Finnish tills - P. Nieminen; A. Kellomäki (Bulletin of the Geological Society of Finland, 1984)
Pore properties of 64 soil samples were studied with mercury porosimetry. The samples were typical Finnish tills and related materials. All samples show porosimetry curves with strong mercury penetration around the pore diameters of 6 μm. This is interpreted to correspond to true pores of that size. The porosity percentage of the samples found by Hg porosimetry is about 50 % of the bulk volume. In addition, there is another ca. 10 % of the volume in the pores with smaller than 6 nm diameters which are inaccessible to mercury. Specific surface areas computed from the Hg porosimetry are of reasonable sizes, about one half of the nitrogen BET areas. For 33 samples the mesopore distributions were computed from water adsorption data. These results roughly agree with the results of Hg porosimetry, but the adsorption method does not yield information about large pores.